Dielectric Networks from solution processed 2D nanomaterials - Nalawade, Yashaswi Sharad (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Shortly after the demonstration of the existence of free-standing graphene, the need for large scale production of two-dimensional nanomaterials was met by the emergence of a solution processing method called liquid phase exfoliation. The versatile and easily scalable nature of this technique made the manufacturing of various nanomaterials instantly more accessible. Furthermore, it wonderfully complimented the growing industry of printed electronics where flexible circuitry required that novel materials be discovered to support increasingly improving device architecture and performance. This synergy has led to numerous published reports where 2D nanomaterial inks are prepared through liquid-phase exfoliation and subsequently printed into devices using various deposition methods developed in parallel. The devices are generally heterostructures made up of stacked nanosheet networks. However, problems arise when attempting to insulate the conducting and semiconducting networks from each other and this is where dielectric films play an important role. For the successful fabrication of stacked heterostructure devices, such as thin-film capacitors or thin-film transistors, it is vital that dielectric networks are uniform and pin-hole free to effectively insulate the various films that make up the device. Discontinuities in the dielectric film can lead to unwanted contacting and shorting of the overall device. Generally, dielectric networks are investigated by incorporating the material in question into a parallel-plate capacitor geometry and analysing its performance. To date, the majority of work on dielectric nanosheet networks has been with hexagonal boronnitride, mainly due to its structural similarity to graphene, low toxicity and abundance. However, it presents several difficulties in that it suffers from a low dielectric constant and forms brittle, highly porous films making it challenging to fabricate an all-printed device. In this vein, we introduce bismuth oxychloride (BiOCl) as a new candidate for dielectric nanosheet films. We report the liquid phase exfoliation of BiOCl into nanosheets for the first time through existing techniques and environmentally friendly solvents. Using aerosol-jet printing (AJP), we fabricate all-printed stacked capacitors of varying thicknesses and identify a minimum insulating thickness of 1.6 μm. With the help of impedance spectroscopy, we model our devices as a Randles circuit in order to extract capacitance values and ultimately the permittivity of the BiOCl nanosheet networks. We obtain areal capacitances ranging from 40 to 110 μF/m2 and a permittivity of εr = 41 ± 3, a significantly higher value than those previously reported for printed dielectric networks. Through breakdown voltage analysis, we deduce a dielectric breakdown strength of 0.67 M V /cm. Thus, we present a new dielectric layered material that is easily exfoliated and can be a good contender for insulating nanosheet networks in printed electronics. Combining different substances to create a composite material has been widely used as a way of enhancing the properties of a system. In particular, conductor-insulator composites have been of interest in the past as a means of improving permittivity. Such composites exhibit a colossal increase in permittivity near the percolation threshold of the conductive filler which is attributed to the formation of several microcapacitors within the system. Motivated by this, we aim to make composite films from 2D nanomaterial inks. While it was demonstrated that an all-printed heterostructure device was achieved through aerosol-jet printing of BiOCl nanosheet ink to obtain a permittivity of 41, AJP is a recent development that involves a vast parameter space, thus lacking a full understanding of the deposition process. Considering the difficulty involved, it is prudent to continue to explore printed dielectric nanosheet networks via a more straightforward deposition method, such as spray coating. We therefore fabricate spray-coated parallel-plate capacitors using BiOCl − Ag nanoplatelet composite inks of varying volume fractions of Ag nanoplatelets. A percolative behaviour was observed as the conductive filler was steadily increased from 0% to 40% with a percolation threshold measured at ≈ 18vol%. This was accompanied by a two-fold increase in the permittivity that illustrated the formation of microcapacitors in the composite system. Although this is a relatively low increase compared to previous theoretical predictions, it can serve as a test-bed for future 2D nanomaterial conductor-insulator composites. An ideal dielectric material is one that displays high electrical resistivity, large di- electric constant and a high dielectric breakdown strength. Unfortunately, instances have shown that the strong electric field created in high-κ dielectrics weakens the polar molecular bonds within the material, which reduces the enthalpy of activation required for dielectric breakdown. Furthermore, dielectric breakdown in thin films is difficult to measure since breakdown first occurs in localised “weak” regions of the film, making it challenging to discern the material’s intrinsic breakdown strength. To adrress this, we present dielectric composites made from 2D nanomaterials. Having established that BiOCl films exhibit significantly higher permittivity than previously reported 2D nano-material dielectric networks, we look towards hBN for its high breakdown strength. By forming a composite using BiOCl and hBN , we aim to produce films that have both large permittivity, and high breakdown strength. The composite inks were deposited into films using a spray-coating method to form an array of capacitors with increasing volume fractions of BiOCl. Impedance spectroscopy was used to extract the permittivity of these composite capacitors. A linear increase in permittivity of the composite films was observed upon the addition of 50 vol% BiOCl reaching a maximum value of 19. While dielectric breakdown measurements posed a logistical challenge, we were able to conclude with preliminary data that the breakdown strength of BiOCl films was improved by the addition of hBN . The highly disordered nature of these films made it challenging to accurately characterise their electrical properties, nonetheless, a proof-of-concept was achieved.
APPROVED